2018
DOI: 10.1002/ccd.27657
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus drug‐eluting stent performance in patients with long coronary lesions: The multicenter Longprime registry

Abstract: In this real-world population, the Xience Prime EES performs extremely well in long lesions, with a very low rate of both MACE and ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Kang et al previously compared the 12-month outcomes of three randomized clinical trials of the LONG-DES (LONG-DES III, IV, and V trials) in percutaneous treatment of LONG native coronary lesions with DES. The comparison of their findings with those of our study is shown in Table 5 [23,[26][27][28][29][30][31][32]. Our MACE outcomes are superior to all studies compared by Kang et al [23].…”
Section: Discussionsupporting
confidence: 52%
“…Kang et al previously compared the 12-month outcomes of three randomized clinical trials of the LONG-DES (LONG-DES III, IV, and V trials) in percutaneous treatment of LONG native coronary lesions with DES. The comparison of their findings with those of our study is shown in Table 5 [23,[26][27][28][29][30][31][32]. Our MACE outcomes are superior to all studies compared by Kang et al [23].…”
Section: Discussionsupporting
confidence: 52%
“…In this study, there were also many diffuse lesions, and the total length of devices in RA/DES group reached 52.16 ± 20.76 mm. Research shows that the implantation of lengthy stents may hinder the stented segment's ability to regain vasomotion, encourage neoatherosclerosis, and restrict access to revascularization [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astonishingly the postdilation rate was between 52 and 66% [2123]. Fernandes et al analyzed a real world population with long coronary lesions after implantation of an everolimus-eluting stent [7]. The MACE and ST rates at 12, and 24-months follow-up were 2.1, 5.4% (MACE) and 0.7, 1.5% (ST) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al analyzed a real world population with long coronary lesions after implantation of an everolimus-eluting stent [7]. The MACE and ST rates at 12, and 24-months follow-up were 2.1, 5.4% (MACE) and 0.7, 1.5% (ST) [7]. The scaffold thrombosis rate in our study was 1.4, 0.0% and for DOCE 8.9, 9.9%, after 12 and 24-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation